Integration of the Pancasila student profile in physical education learning - Nopiyanto, Yahya Eko; Pujianto, Dian; Maisarah, Ira; Wibowo, Cahyo; Kardi, Ipa Sari (Edu Sportivo: Indonesian Journal of Physical Education, 2024)
Background: The integration of the Pancasila Student Profile (PSP) in physical education (PE) learning represents a significant endeavour to align educational practices with national values and aspirations. Through rigorous research and thoughtful implementation strategies, educators can harness the transformative potential of PE to cultivate socially responsible citizens who embody the spirit of Pancasila in their actions and interactions within the broader Indonesian society. Research Objectives: The aim of this research is to determine the level of integration of Pancasila student profiles in physical education learning in Bengkulu City. Methods: The quantitative research method was used to achieve this goal. The sample was 432 students whose taken randomly among the elementary school, middle school, and high school. The instrument in this research was a questionnaire. The data was analysed using the mean ideal and the deviation standard ideal. Finding/Results: The integration of the PSP in schools in the city of Bengkulu has four different categories. In the very high category, the frequency is 51; in the high category, the frequency is 301; in the moderate category, the frequency is 78; and in the low category, the frequency is 2. Conclusion: The Pancasila profile of students learning PE in Bengkulu City is well implemented. The novelty of integrating the PSP into PE learning lies in its unique approach to instilling national values and character education in the PE curriculum. This integration aims to encourage holistic student development by combining physical education learning with the values of God Almighty, independence, global diversity, cooperation, critical thinking, and creative thinking, which are the core of the Pancasila student profile.